(untitled) (International relations and international law Journal, 2016)
USA versus China. Today we have a lot of question about future of the world, future of international relation and future of the humanity. Who is going to lead people in the future? Can China surpass US or not? Is it going to be the war between both countries? Will China become a superpower in the next decade? XXI century preparing us more questions than answers. US opinions have divided into two views. The US military and its proxies describe China as a more than a rival – as a looming threat. Others, most especially Wall Street, see China as about to slide into recession. Or depression. Or sink into the sea, like Atlantis. They describe two different worlds, both shaped by American needs and fears. What can China achieve in the nearest future? What is the reality? Today a lot of experts and scholars debate on this questions every time. Each debate opens us new reality which we couldn’t even imagine…